Common determinants of bond and stock market liquidity: The impact of financial crises, monetary policy, and mutual fund flows - Tarun Chordia; Asani Sarkar; Avanidhar Subrahmanyam (Federal Reserve Bank of New York, 2001)
We study common determinants of daily bid-ask spreads and trading volume for the bond and stock markets over the 1991-98 period. We find that spread changes in one market are affected by lagged spread and volume changes in both markets. Further, spread and volume changes are predictable to a considerable degree using lagged market returns, lagged interest rates, lagged spreads, and lagged volume. During periods of financial crisis, stock and bond spreads and volume are more volatile and become more highly correlated; moreover, at these times, money supply positively affects financial market liquidity, albeit with a lag of two weeks. During normal times, increases in mutual fund flows enhance stock market liquidity and trading volume, but during financial crises, U.S. government bond funds see higher inflows, resulting in increased bond market liquidity. Overall, this study deepens our understanding of the dynamics of liquidity in financial markets and suggests how asset allocation strategies might be designed to reduce trading costs.
Keywords: G10; G14; G23; E52; 330; Gesamtwirtschaftliche Liquidität; Aktienmarkt; Rentenmarkt; Börsenumsatz; Bid-Ask Spread; USA